Interpersonal Communication and Situational Leadership on Teacher Performance - A. Samad, M. Yusuf; Fauzi, Fauzi; Marhamah, Marhamah; Rahmani, Shafira Ulfa (Jurnal Ilmu Komunikasi, 2023)
Teacher performance plays a very important role in improving the quality of learning and the quality of graduatesdetermined by interpersonal communication and situational leadership of the principal. This study aims toanalyze the influence of interpersonal communication and situational leadership of the principal on teacherperformance at SD IT Bunayya Lhokseumawe. The research method uses correlational, with a quantitativeapproach. Data collection used a questionnaire distributed to 38 respondents as a total sample. The measurementscale uses a Likert scale of four answer choices. This study used multiple linear regression analysis. Previously,prerequisite analysis tests were carried out using tests of data normality, autocorrelation, heteroskedasticity andmulticollinearity. The results of the study stated that teacher performance was significantly and simultaneouslyinfluenced by interpersonal communication and situational leadership of the principal by 70.7 percent and theremaining 29.3 percent was influenced by other variables that were not studied. Research contribution to theprincipal to open communication in providing positive responses and attitudes to teachers. The principal placeshimself according to the teacher’s situation so that he can foster good cooperation. Teacher performance improvesas seen from the learning process by compiling and mastering the material and skillfully using learning media.